2012
DOI: 10.1167/iovs.11-9272
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-328 May Influence Myopia Development by Mediating thePAX6Gene

Abstract: We elaborated the relationship among myopia development, SNP rs662702, microRNA-328 and RA. The data imply that reduction of miR-328 and/or RA can be potential strategies for myopia prevention or treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 27 publications
(36 reference statements)
0
57
0
1
Order By: Relevance
“…As expected, miR-335 overexpression significantly downregulated the protein expression of PAX6, while inhibition of miR-335 promoted the protein level of PAX6 in U87 and U251 cells, which are WHO IV grade. In fact, several other miRNAs have also been reported to directly target PAX6, including miR-290-295, miR-365-3p and miR-328 (29)(30)(31). Huang et al demonstrated that miR-223 promoted the growth and invasion of glioblastoma cells by targeting PAX6 (32).…”
Section: Discussionmentioning
confidence: 99%
“…As expected, miR-335 overexpression significantly downregulated the protein expression of PAX6, while inhibition of miR-335 promoted the protein level of PAX6 in U87 and U251 cells, which are WHO IV grade. In fact, several other miRNAs have also been reported to directly target PAX6, including miR-290-295, miR-365-3p and miR-328 (29)(30)(31). Huang et al demonstrated that miR-223 promoted the growth and invasion of glioblastoma cells by targeting PAX6 (32).…”
Section: Discussionmentioning
confidence: 99%
“…36 Our recent study also indicated that TGF-b signaling could play a role in the development of myopia. 29 Hence, FGF10 is likely to have involved in the development of myopia by mediating TGF-b signaling to further remodel ECM.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] In our previous study of microRNA-328, retinoic acid, and TGF-b were shown to be involved in the same network regulation leading to the development of myopia. 29 A recent study indicated that retinoic acid could regulate the TGFb pathway in the control of FGF10 expression. 30 Therefore, the present study focuses on the involvement of FGF10 in the development of myopia.…”
mentioning
confidence: 99%
“…A study from Taiwan revealed that miRNA may play a role in the regulation of the PAX6 gene [29]. miR-328 was predicted to bind to 3′-UTRs of PAX6 transcripts.…”
Section: Mirnas and Eye Disordersmentioning
confidence: 99%